New approach to simplifying and optimising acute malnutrition treatment in children aged 6–59 months: the OptiMA single-arm proof-of-concept trial in Burkina Faso. Issue 7 (14th April 2020) - Daures, Maguy; Phelan, Kevin; Issoufou, Mariama; Kouanda, Séni; Sawadogo, Ousmane; Issaley, Kader; Cazes, Cecile; Séri, Benjamin; Ouaro, Bertine; Akpakpo, Bruno; Mendiboure, Vincent; Shepherd, Susan; et al.
Abstract: The Optimising treatment for acute MAlnutrition (OptiMA) strategy trains mothers to use mid upper arm circumference (MUAC) bracelets for screening and targets treatment to children with MUAC < 125 mm or oedema with one therapeutic food at a gradually reduced dose. This study seeks to determine whether OptiMA conforms to SPHERE standards (recovery rate > 75 %). A single-arm proof-of-concept trial was conducted in 2017 in Yako district, Burkina Faso including children aged 6–59 months in outpatient health centres with MUAC < 125 mm or oedema. Outcomes were stratified by MUAC category at admission. Multivariate survival analysis was carried out to identify variables predictive of recovery. Among 4958 children included, 824 (16·6 %) were admitted with MUAC < 115 mm or oedema, 1070 (21·6 %) with MUAC 115–119 mm and 3064 (61·8 %) with MUAC 120–124 mm. The new dosage was correctly implemented at all visits for 75·9 % of children. Global recovery was 86·3 (95 % CI 85·4, 87·2) % and 70·5 (95 % CI 67·5, 73·5) % for children admitted with MUAC < 115 mm or oedema. Average therapeutic food consumption was 60·8 sachets per child treated. Recovery was positively associated with mothers trained to use MUAC prior to child's admission (adjusted hazard ratio 1·09; 95 % CI 1·01, 1·19). OptiMA was successfully implemented at the scale of an entire district under 'real-life' conditions. Programme outcomes exceeded SPHERE standards, but further study is needed to determine if increasing therapeutic food dosages for the most severely malnourished will improve recovery.